х=5.4
Пошаговое объяснение:
-4.5(х-3)-1=7.2-5(х-2)
-4.5х+13.5-1=7.2-5х+10
-4.5х+5х=7,2+10-13.5-1
0.5х=2.7
отметь как лучший ответ)
-4,5(х-3)-1=7,2-5(х-2)
-4,5x + 13,5 - 1 = 7,2 - 5x + 10
-4,5x + 12,5 = 17,2 - 5x
5x - 4,5x = 17,2 - 12,5
0,5x = 4,7
x = 4,7 : 0,5
x = 9,4
х=5.4
Пошаговое объяснение:
-4.5(х-3)-1=7.2-5(х-2)
-4.5х+13.5-1=7.2-5х+10
-4.5х+5х=7,2+10-13.5-1
0.5х=2.7
х=5.4
отметь как лучший ответ)
Пошаговое объяснение:
-4,5(х-3)-1=7,2-5(х-2)
-4,5x + 13,5 - 1 = 7,2 - 5x + 10
-4,5x + 12,5 = 17,2 - 5x
5x - 4,5x = 17,2 - 12,5
0,5x = 4,7
x = 4,7 : 0,5
x = 9,4